Dunn analysis on indonesian energy policy - Dwiani, Ery; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2018)
Abstract – National Energy Policy and National Energy General Plan have been established. However, after 4 (four) years National Energy Policy was published, there are several problem occurs in energy sector. As a result, the effectiveness of this policy is still remained to be seen. Government needs to make another intervention to follow up the issue. Therefore an objective study is needed on the evaluation of National Energy Policy, National Energy General Plan and the formulation of Regional Energy Plan. This final project is carried out by using the Policy Analysis method according to William Dunn by comparing the policy that has been established with the results of the interview on the condition at this time. The gap is a problem that requires an appropriate solution in implementing the established policy and the preparation of the Regional General Energy Plan as a form of implementation of the National Energy Policy and the National General Energy Plan. The results of the analysis show that there are problems in implementing the National Energy Policy and General Plan of National Energy, among others: 1) After 4 (four) years determined, the electrification ratio of Indonesia which still has not reached 100%; 2) Policies on the Buffer Stock of Energy have not existed; 3) There is still a lack of understanding of both the community and local government regarding the importance of energy roles; 4) The Regional General Energy Plan has not been set; 5) Limited budget and human resources of local government; and 6) Lack of communication and coordination between government and local government. In general, the National Energy Policy and the General Plan of National Energy have a good purpose and should proceed. Based on the analysis, then formulated the solution that must be taken by the Government to improve the situation, among others: 1) The Government assists the Regional Government in the preparation of the General Plan of Regional Energy; 2) Increasing people's understanding of the importance of energy role by implementing socialization on a large scale; 3) Consistency of Regional Government in energy development priority that will be poured in General Plan of Regional Energy; 4) Improved coordination between the Government and Local Government; 5) Changing the energy planning paradigm from supply side to demand side that is based on requirement from region; 6) RUED is expected to increase the industrial sector in the region 7) Review of energy policy.Keywords:  National Energy Policy, National Energy General Plan, Regional Energy Policy, Dunn Policy Analysis.